Understanding Relationships and Remittance Flow During the Migration Period: Strength of Social Ties as a Factor Determining Remittance Behaviour - Mukwembi, Thebeth, R; Maharaj, Pranitha (African Human Mobility Review, 2021)
Remittances transferred between migrants and non-migrants play a major role in alleviating poverty and improving social and economic well-being in many developing countries. Although remittances are regarded as an outcome of migration with far reaching effects as a livelihood strategy, not all non-migrants with migrant family members are recipients of remittances. Remittances are not transferred to all non-migrant family members in the country of origin. Migrants identify particular individuals as recipients of remittances, which they send to their home countries during the migration period. Therefore, it is important to understand the determinants of remittance flow and remittance behaviour during the migration period. This study explores relationships between migrants and non-migrants and how such relations influence the flow of remittances during the migration period. A qualitative approach was employed in which 60 interviews were conducted (30 with Zimbabwean migrants in Durban and 30 with their respective family members in Zimbabwe). The study found that the strength of social ties between migrants and non-migrants plays a major role in determining remittance flows.